2022
DOI: 10.3390/children9091292
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Ventilation in Preterm Infants: Factors Influencing Weaning Decisions and the Role of the Silverman-Andersen Score

Abstract: The factors influencing weaning of preterm infants from noninvasive ventilation (NIV) are poorly defined and the weaning decisions are often driven by subjective judgement rather than objective measures. To standardize quantification of respiratory effort, the Silverman-Andersen Score (SAS) was included in our nursing routine. We investigated the factors that steer the weaning process and whether the inclusion of the SAS would lead to more stringent weaning. Following SAS implementation, we prospectively evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…The poor inter-rater agreement indicates that the use of the SA index might not provide enough information to identify when to scale up and when to start weaning from respiratory support. Nussbaum et al showed that low SA index scores did not necessarily lead to weaning from NIV, yet higher scores were predictive against weaning [11]. The authors highlighted that bradycardias, apneas and desaturations might have a higher impact on the weaning decision than low scores of respiratory distress [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The poor inter-rater agreement indicates that the use of the SA index might not provide enough information to identify when to scale up and when to start weaning from respiratory support. Nussbaum et al showed that low SA index scores did not necessarily lead to weaning from NIV, yet higher scores were predictive against weaning [11]. The authors highlighted that bradycardias, apneas and desaturations might have a higher impact on the weaning decision than low scores of respiratory distress [11].…”
Section: Discussionmentioning
confidence: 99%
“…Nussbaum et al showed that low SA index scores did not necessarily lead to weaning from NIV, yet higher scores were predictive against weaning [11]. The authors highlighted that bradycardias, apneas and desaturations might have a higher impact on the weaning decision than low scores of respiratory distress [11]. It is possible that the SA index is more useful in an "either-or" situation regarding whether the preterm infants need respiratory support or not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each category was scored from 0 to 2, with an infant breathing comfortably receiving a score of “0” and an infant in severe respiratory distress receiving a score of “10” point 12,13 . For the SAS, 0‐2 points were accepted as no/mild respiratory distress, 3 points as moderate respiratory distress and SAS ≥ 4 points as significant respiratory distress as it has been reported by Nussbaum et al 14 All infants with a SAS score ≥3 points received standardized noninvasive ventilatory support as nasal continuous positive airway pressure (n‐CPAP) with a positive end‐expiratory pressure (PEEP) of 6 cmH 2 O. Infants <35 weeks of gestational age, infants with congenital malformations and whose parents disagreed to participate were all excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Each category was scored from 0 to 2, with an infant breathing comfortably receiving a score of "0" and an infant in severe respiratory distress receiving a score of "10" point. 12,13 For the SAS, 0-2 points were accepted as no/mild respiratory distress, 3 points as moderate respiratory distress and SAS ≥ 4 points as significant respiratory distress as it has been reported by Nussbaum et al 14…”
Section: Introductionmentioning
confidence: 99%